Developing a Utilisation of WAQF Property and Governance Framework by Mutawalli - Maamor, Selamah; Abd Mutalib, Hasyeilla; Hashim, Suraiya; Abd Wahab, Norazlina; Zainol, Zairy; Shakrani, Mohd Saharudin (The Mattingley Publishing Co., Inc., 2020)
Most of the waqf property in Malaysia is managed and governed entirely by the State Islamic Religious Council (SIRC) because all of SIRCs is the sole trustee at the state level. Every SIRC has their own state's enactment, regulation and procedure to manage all the waqf institutions and resulted in different practices to all states in Malaysia. Islamic law stated that the waqf property must be managed, administrated and supervised by the pertinent parties or institutions called Al-Mutawalli whereby it can be a person, a group of people or an institution. Therefore, the purpose of this study is to develop a framework on the waqf property utilisation and governance practised by institutional mutawalli in Malaysia. This study employs qualitative methods by investigating five selected institutional mutawalli in Malaysia in term of their utilisation and governance practised. This study has performed a formal and semi-structured interview with waqf manager, deputy CEO, waqf coordinator and manager of the waqf development unit as a representative to the institutional mutawalli. Framework on Utilisation of Waqf Property and Governance is a structure of utilising waqf property by the institutional mutawalli (IM) which involves five components. The five components are input, process, output, governance and roles, responsibility and accountability. This framework disseminates the importance of utilisation and governance in waqf property management structure to enhance better administration and management of institutional mutawalli towards the utilisation of the waqf property. Thus, from the information, each institutional mutawalli can take proactive action to ensure all waqf properties in their institution is well managed, administered and developed accordingly as it can contribute to the socio-economic of Ummah